Le cliffhanger : un révélateur des fonctions du récit mimétique - Raphaël Baroni (Cahiers de Narratologie, 2016)
Cliffhanger is a narrative technique based on the interruption of a narrative when a tension is created, calling for urgent resolution. It involves a desynchonization of textual closure and of resolution of plot. This paroxysmal suspension can be based on the arousal of suspense or curiosity and it is often accompanied by an explicit presentation of unresolved uncertainties, and by metadiegetic comments inviting the receiver to wait for the next developments of the story. The break is usually associated with a periodical publication, but one can find traces of it in chapters of a novel or in the succession of pages in comics previously published in a serialized form. There are also cliffhangers in folktales, as evidenced by the suspenseful stories of Scheherazade in The 1001 Nights. Cliffhanger can be considered as a commercial technique, but it also highlights some of the key features of mimetic narratives, which appear as representations of events rooted in experienciality, where the storyworld appears as an ontologically unstable matrix of virtualities corresponding to plot in its unresolved status. As illustrated by a comparison with serialized informations in news media, this perspective offers a simulation of events involving the ethical or political responsibility of the subject.